Pseudocyst of the pancreas due to acute hemorrhagic pancreatitis in children - Benedetti, Juan Luis; Campos, Néstor; Chavarría, Oscar (Cirugía del Uruguay, 1986)
Acute pancreatitis in the ehild is a pathology nol too fraquent. But even so, ihene .er pa n is present, especially in the supraumbilica area, it is necessary lo make a dosilication of amylase i he blood for an early investlgation of possible pancreatic etiology.